Structured Scientific Methodologies in Maritime Product and Service Innovation: Enhancing Evidence-Based Decision-Making - Nooh Isman Sarante; Putri Agil Alamanda; Ravinda Dwi A. S.; Renanda Aurelia Putri; Rizky Nu'aldira; ⁠Suwarti ⁠Suwarti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The maritime industry is undergoing rapid transformation, requiring systematic, evidence-based methodologies to improve product and service innovation success rates. Traditionally, maritime businesses have relied on intuition-based decision-making, leading to inefficiencies, increased risks, and inconsistent innovation outcomes. This study investigates the role of structured scientific methodologies in maritime innovation management, emphasizing how systematic approaches enhance decision accuracy, minimize risk, and improve long-term sustainability. This research provides original value by evaluating the effectiveness of structured scientific approaches in maritime innovation, an area where limited studies have explored the intersection of philosophy, leadership, and evidence-based decision-making. The study addresses the following research questions: To what extent do structured scientific methodologies improve product and service innovation success? How do industry leaders, lecturers, and students perceive the role of evidence-based decision-making in innovation?Using qualitative research methods, the study collected data from maritime experts, lecturers, and postgraduate students through semi-structured interviews and document analysis, followed by thematic and comparative analysis. Results indicate that structured methodologies significantly improve innovation outcomes, but barriers such as industry reluctance and lack of competency development hinder adoption. The study concludes that integrating scientific reasoning into maritime leadership training can enhance innovation success, mitigate risk, and foster a culture of evidence-based strategic management.